Studi Literatur: Manajemen Pendidikan Berbasis Kearifan Lokal Banjar dalam Penguatan Karakter Siswa - Verdian Wirtung; Ana Fitrotun Nisa (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Character education is a key pillar of the Indonesian education system. Technological developments and the rapid flow of globalization pose significant challenges to the character development of students, particularly in the era of information disruption, which often shifts the nation's moral values. Schools are expected to serve not only as institutions for the transfer of knowledge but also as centers for the formation of noble personalities. One strategic approach to strengthening character education is the integration of local wisdom. Banjar traditions such as the "kayuh baimbai" (mutual cooperation), "badamai" (peaceful deliberation), and the "Batamat Al-Qur'an" (Batamat Al-Qur'an) embodied values ​​of religiosity, responsibility, tolerance, and respect for parents and teachers. This study used the Systematic Literature Review (SLR) method by examining primary articles related to character education based on local wisdom, particularly in the Banjar community. The analysis shows that local culture-based educational management can be a more contextual and applicable learning alternative, and supports the strengthening of student identity. The study also highlights obstacles such as teachers' limited understanding of local culture, the lack of integration of local wisdom values ​​into the curriculum, and weak infrastructure support. Thus, the integration of local wisdom is not only relevant for strengthening character but also as a strategy for maintaining cultural identity amidst globalization.